The potential of liquid smoke as an oral ulcer remedies: A proposed mechanism based on systematic review. - Meircurius D.C. Surboyo; Diah S. Ernawati; Ira Arundina; Dieni Mansur; Benni Iskandar; Arvind B.R. Santosh; Kelvin A.N. Anggrarista; Pamela H. Cecilia; Ayu A.B. Nagoro (GarVal Editorial Ltda., 2021)
Context: The standard management of oral ulcer therapy is focused only on symptomatic therapy, such as reducing pain. To date, there is no topical drug that has the pharmacodynamics to intervene in oral ulcer pathogenicity. Liquid smoke is traditionally used as a safe natural preservative. The liquid smoke is highly phenolic and compound rich. It is presumed to have analgesic and anti-inflammatory effects with potentially promising therapeutic effects on oral ulcers. Aims: To describe the possible pharmacodynamics or action mechanism of liquid smoke as a promising remedy for oral ulcer therapy. Methods: A comprehensive literature review on PubMed, ScienceDirect, Scopus and Embase was performed using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The keywords used included 'liquid smoke', 'wood vinegar', 'liquid pyrolysis' and 'oral ulcer'. A screening process, including titles, abstracts and full texts, was performed. Eight related articles were selected to describe the possible pharmacodynamics or mechanism action of the liquid smoke originating from coconut shells and rice hulls for oral ulcer remedies. Results: Liquid smoke from coconut shell and rice husk is highly contained phenol, guaiacol and 2-methoxy-5-methylphenol (2-EMP). These compounds are antioxidants that can bind reactive oxygen species and increase cellular responses, inhibiting nuclear factor-kappa B activation and pro-inflammatory cytokine production while increasing macrophage differentiation to M2. The increase of M2, with help from lymphocytes, can secrete various growth factors, which can accelerate the proliferation of fibroblasts and collagens needed in the healing process of oral ulcers. Conclusions: Liquid smoke pharmacodynamics inhibit both inflammatory and proliferation pathway stimulation, which promises remedies for oral ulcers.